PELUANG DAN TANTANGAN PENGUSAHA KERUPUK DALAM MENINGKATKAN PRODUKTIVITAS USAHA (Studi Di UD Mekarsari Desa Benda Kecamatan Karangampel Kabupaten Indramayu) - Nuraeni; Euis Puspitasari; Rijal Assidiq Mulyana (PT. Hasba Edukasi Mandiri, 2025)
This study aims to examine the opportunities and challenges of crackers entrepreneurs in increasing business productivity at UD Mekarsari, Benda Village, Karangampel District, Indramayu Regency. This cracker business has been established for more than 15 years and involves local communities in its production process. The research method used is qualitative with a case study design. Data were collected through observation, interviews, and documentation, then analyzed using Miles and Huberman’s model through data reduction, data display, and conclusion drawing. The results show that business opportunities lie in high market demand, availability of raw materials, local labor, and product variations. Meanwhile, the challenges include limited capital, weather conditions, rising raw material prices, competition, and limited digital marketing. In conclusion, UD Mekarsari still has great opportunities to grow by maintaining product quality, innovating, and utilizing digital technology in marketing.